Effects of Mucilage on Rhizosphere Hydraulic Functions Depend on Soil Particle Size - Kroener, Eva; Holz, Maire; Zarebanadkouki, Mohsen; Ahmed, Mutez; Carminati, Andrea (Vadose zone journal, 2018)
Core Ideas We propose a model of mechanistic pore‐scale interactions of mucilage, water, and soil. Effect of mucilage on saturated hydraulic conductivity is stronger in coarse soils. Coarse soils require higher mucilage concentration to increase water content. Upscaling to macroscopic soil hydraulic properties remains challenging. The model was validated on measured water retention and saturated hydraulic conductivity Mucilage secreted by roots alters hydraulic properties of soil close to the roots. Although existing models are able to mimic the effect of mucilage on soil hydraulic properties for specific soils, it has not yet been explored how the effects of mucilage on macroscopic soil hydraulic properties depend on soil particle size. We propose a conceptual model of how mechanistic pore‐scale interactions of mucilage, water, and soil depend on pore size and mucilage concentration and how these pore‐scale characteristics result in changes of macroscopic soil hydraulic properties. Water retention and saturated hydraulic conductivity of soils with different ranges of particle sizes mixed with various mucilage concentrations were measured and used to validate the conceptual model. We found that (i) at low mucilage concentrations, the saturated conductivity of a coarse sand was a few orders of magnitude higher than that of a silt, (ii) at an intermediate concentration, the hydraulic conductivity of a fine sand was lower than of a coarse sand or a silt, and (iii) at a high concentration, all soils had a hydraulic conductivity of the same magnitude. At low matric potentials, mucilage increased the water content in all soilsin all soils. In coarser soils, higher mucilage concentrations were needed to induce an increase in water content of >0.05 g g–1 at low matric potentials. This study shows how pore‐scale interactions between mucilage, water, and soil particles affect bulk soil hydraulic properties in a way that depends on soil particle size. Including such effects in quantitative models of root water uptake remains challenging.